Role of Stocktaking Application using Barcode Scanning in Improving Stock Conformity in Hospital Pharmacy Installation - Halim, Ratna Suryati; Fitriasari, Nikma (Fakultas Kedokteran Universitas Brawijaya, 2021)
One of the most important managerial activities for hospitals is an internal control activity for drug supplies, including during the Covid-19 pandemic. A preliminary study at Graha Sehat Medika hospital (GSM hospital) showed that the inaccuracy of stocktaking results in the last six months was 40% -70%. The solution taken is the use of